Polymorphisms in Genes of Lipid Metabolism Are Associated with Type 2 Diabetes Mellitus and Periodontitis, as Comorbidities, and with the Subjects’ Periodontal, Glycemic, and Lipid Profiles - Ingra G. Nicchio; Thamiris Cirelli; Rafael Nepomuceno; Marco A. R. Hidalgo; Carlos Rossa; Joni A. Cirelli; Silvana R. P. Orrico; Silvana P. Barros; Letícia H. Theodoro; Raquel M. Scarel-Caminaga (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus (T2DM) and periodontitis (P) commonly occur as comorbidities, but the commonalities in the genetic makeup of affected individuals is largely unknown. Since dyslipidemia is a frequent condition in these individuals, we investigate the association of genomic variations in genes involved in lipid metabolism with periodontal, glycemic, lipid profiles, and the association with periodontitis and T2DM (as comorbidities). Methods. Based on clinical periodontal examination and biochemical evaluation, 893 subjects were divided into T2DM+P (T2DM subjects also affected by periodontitis, n=205), periodontitis (n=345), and healthy (n=343). Fourteen single-nucleotide polymorphisms (SNPs) were investigated: LDLR gene (rs5925 and rs688), APOB (rs676210, rs1042031, and rs693), ABCC8 (rs6544718 and 6544713), LPL (rs28524, rs3735964, and rs1370225), HNF1A (rs2650000), APOE (rs429358 and rs7412), and HNF4A (rs1800961). Multiple linear and logistic regressions (adjusted for covariates) were made for all populations and stratified by sex and smoking habits. Results. Individuals carrying APOB-rs1042031-CT (mainly women and never smokers) had a lower risk of developing periodontitis and T2DM (T2DM+P); altogether, this genotype was related with healthier glycemic, lipid, and periodontal parameters. Significant disease-phenotype associations with gene-sex interaction were also found for carriers of APOB-rs1676210-AG, HNF4A-rs1800961-CT, ABCC8-rs6544718-CT, LPL-rs13702-CC, and LPL-rs285-CT. Conclusions. Polymorphisms in lipid metabolism genes are associated with susceptibility to T2DM-periodontitis comorbidities, demonstrating gene-sex interaction. The APOB-rs1042031 was the most relevant gene marker related to glucose and lipid metabolism profiles, as well as with obesity and periodontitis.